A comparison of tadpoles of two populations of Leptodactylus plaumanni (Anura: Leptodactylidae), with a discussion of Leptodactylus tadpole morphology. (2nd September 2018) - Mello, Caio Marinho; Gonçalves, Darlene da Silva; Solé, Mirco; Rossa-Feres, Denise de Cerqueira; Conte, Carlos Eduardo
ABSTRACT: Of the currently known 75 species within the four recognized species groups of Leptodactylus, the L. fuscus group contains 30 species, of which tadpoles are known for 24, including L. plaumanni described based on a population from Argentina. Herein, we describe external and internal oral morphology of L. plaumanni tadpoles collected in Brazil and compare with tadpoles from Argentina. In addition, we compare phenetic groups obtained from analysis of larval characters with the currently recognized species groups. The tadpole of L. plaumanni from Brazil is identified by: body globular in lateral view, ventral fin forming a wide arc, oral disc lateroventrally emarginate, marginal papillae of oral disc biseriate, more than 10 papillae on each side delimiting the mouth floor, and buccal roof arena trapezoidal. Of the 23 analyzed external morphological characters, only eight were shared by tadpoles from Argentina and Brazil, and they also shared 14 of the 15 internal oral morphological characters. Tadpoles of both populations differ in external morphology and, although such intraspecific differences can be due to plasticity, the hypothesis that these two populations represent different species cannot be dismissed. Phenetic groups obtained using larval characters are consistent with species groups proposed for Leptodactylus by phylogenetic analysis, based on adult characters.